3‐Methylcyclohex‐2‐en‐1‐one reduces the aggregation of Dendroctonus pseudotsugae barragani and corresponding mortality of Pseudotsuga menziesii in northern Mexico. (14th March 2022) - Sánchez‐Martínez, Guillermo; Mehmel, Constance J.; González‐Gaona, Ernesto; Mori, Sylvia R.; López‐Hernández, Juan Antonio; Monárrez‐González, José Carlos; García‐Rodríguez, José Leonardo; Mejía‐Bojórquez, Jorge Manuel; Gillette, Nancy E.
Abstract: Dendroctonus pseudotsugae is the most important forest insect pest of Douglas‐fir Pseudotsuga menziesii in North America. Two subspecies of Douglas‐fir beetle are recognized: D . pseudotsugae pseudotsugae, which inhabits southwestern Canada and western United States, and Dendroctonus pseudotsugae barragani, which occurs in northern Mexico. This study aimed to determine the effectiveness of 3‐methylcylohex‐2‐en‐1‐one (MCH) in reducing aggregation of D . pseudotsugae barragani, and corresponding Douglas‐fir mortality by this insect. Two field experiments were conducted: the first consisted of three doses of MCH in bubble caps (plus a control treatment) applied within 16 0.5 ha plots. The second consisted of three doses of MCH disrupt micro‐flakes (plus a control treatment) applied within 16 1.0 ha plots. MCH bubble caps at 28.8 and 44.0 g AI/ha and MCH disrupt micro‐flakes at 185.3 and 741 g AI/ha significantly reduced the aggregation of D . pseudotsugae barragani . When applying MCH as bubble caps, only the highest dose (44.0 g AI/ha) significantly reduced the number of successfully attacked trees. However, MCH micro‐flake doses of 185.3 and 741 g AI/ha reduced the number of successfully attacked trees to zero.